2004
DOI: 10.1111/j.1365-2044.2004.03670.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based strategies for preventing drug administration errors during anaesthesia

Abstract: SummaryWe developed evidence-based recommendations for the minimisation of errors in intravenous drug administration in anaesthesia from a systematic review of the literature that identified 98 relevant references (14 with experimental designs or incident reports and 19 with reports of cases or case series). We validated the recommendations using reports of drug errors collected in a previous study. One general and five specific strong recommendations were generated: systematic countermeasures should be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(158 citation statements)
references
References 99 publications
3
146
0
9
Order By: Relevance
“…Our observation that anesthesia providersin-training tend to report these errors more often than experienced providers also suggests that more focused education in management and administration is desirable to minimize medication errors/pre-errors during the early part of specialty training. 25 In conclusion, reports of medication errors/pre-errors continue to occur in the practice of anesthesiology. Although our reporting incidence rates were similar to those of other studies, we also observed that surgical case type, patient ASA classification, and the level of provider experience play a role in the frequency of medication errors/pre-errors in a large academic teaching hospital.…”
Section: Resultsmentioning
confidence: 93%
“…Our observation that anesthesia providersin-training tend to report these errors more often than experienced providers also suggests that more focused education in management and administration is desirable to minimize medication errors/pre-errors during the early part of specialty training. 25 In conclusion, reports of medication errors/pre-errors continue to occur in the practice of anesthesiology. Although our reporting incidence rates were similar to those of other studies, we also observed that surgical case type, patient ASA classification, and the level of provider experience play a role in the frequency of medication errors/pre-errors in a large academic teaching hospital.…”
Section: Resultsmentioning
confidence: 93%
“…Such errors, which occur at a rate of about 1 per 130-450 patients, [7][8][9][10][11] are associated with increases in morbidity, mortality, and the costs of hospital care. [8][9][10][11][12] Fortunately, most anesthetic-related errors are inconsequential; however, some lead to substantial or permanent injury and even death. 8,13 In this review, we focus on systems designed to reduce medication errors in the operating room and highlight three Canadian initiatives: 1) systematic efforts to improve the labelling of drug ampoules and vials, 2) introduction of bar-coding in medication systems, and 3) novel tools for ''reconciliation'' or for accurate documentation and adjustment of patients' medication taken before and during their hospital stay.…”
Section: Résumémentioning
confidence: 99%
“…This article concludes with a description of emerging issues for drug safety in anesthesia. Readers interested in more comprehensive reviews of medication errors in anesthetic practice are referred to other articles 12,14 and recommendations. [14][15][16][17][18] Medication safety in anesthesia…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Our records also indicate that reports of inaccurate invasive pressure readings are extremely rare. Additionally, invasive methods typically show more consistency than non-invasive methods for reading arterial pressure [1].…”
Section: A Replymentioning
confidence: 99%